Aplikasi Pemesanan Jasa Fotografi & Wedding Venue di Bali Berbasis Website - Rifky Lana Rahardian; Ni Kadek Reva Deandary; Milla Kusuma Dewi (Politeknik Negeri Cilacap, 2021)
Bali offers so many beautiful places that can be used as references to capture important moments in one's life, one of which is the moment to make a sacred promise. However, there is no liaison media that makes it easier to bring together consumers, photography service companies and venues because the marketing is still done conventionally which is not equipped with transaction features which is quite difficult, not only from potential customers but also service owners. Therefore, this research was made using the sequential linier approach method to facilitate ordering services, determining the location according to customer desires, increasing regional income by collaborating with venue providers on the island of Bali and also helping companies to facilitate marketing with a wider scope by ease of ordering and transactions through the website which is certainly more efficient and effective compared to conventional methods.